Pelatihan Implementasi Tata Kelola Organisasi Yang Baik Bagi Organisasi Non Profit Di Surabaya - Sri Yunan Budiarsi; Dominicus Wahyu Pradana; Daniel Tulasi (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Social organization is an association, namely a group of people who have the same goals, interests, hobbies, and interests and form a permanent organization. This training is intended for the management of the Nekafmese organization, which is a community of immigrants from NTT. The benefits that can be taken from this training are: the management knows the basics of good organiza-tional management, the management knows how to prepare organi-zational equipment such as vision, mission, goals, activity plans, and SOP. The training method used is Asset-Based Community Devel-opment (ABCD), because it is considered the right approach to the problems encountered in the Nekaf Mese Organization. The results of the training show that based on the feedback, responses, and partici-pation of all leaders and members of the Nekaf Mese Surabaya organ-ization, it can be concluded that the participants are satisfied with the training activities and require regular and sustainable training from the Community Service Team